Knowledge, attitude and practices of pregnant women related to COVID‐19 infection: A cross‐sectional survey in seven countries from the Global Network for Women's and Children's Health. (10th March 2022) - Naqvi, Farnaz; Naqvi, Seemab; Billah, Sk Masum; Saleem, Sarah; Fogleman, Elizabeth; Peres‐da‐Silva, Nalini; Figueroa, Lester; Mazariegos, Manolo; Garces, Ana L.; Patel, Archana; Das, Prabir; Kavi, Avinash; et al.
Tweetable abstract: Pregnant women in 7 low and middle income sites often had incomplete knowledge related to COVID‐19 and practices to prevent COVID‐19 during pregnancy varied. Abstract: Objective: We sought to understand knowledge, attitudes and practices (KAP) regarding COVID‐19 in pregnant women in seven low and middle‐income countries (LMIC). Design: Population‐based prospective, observational study. Settings: Study sites in DRC, Kenya, Zambia, Bangladesh, India (two sites), Pakistan and Guatemala. Population and sample: Pregnant women in the Global Network's Maternal and Neonatal Health Registry (MNHR). Methods: A KAP questionnaire was administered in face‐to‐face interviews with pregnant women from September 2020 through October 2021 in the MNHR. Main outcome measures: KAP regarding COVID‐19 during pregnancy. Results: In all, 25 260 women completed the survey. Overall, 56.8% of women named ≥3 COVID‐19 symptoms, 34.3% knew ≥2 transmission modes, 51.3% knew ≥3 preventive measures and 79.7% named at least one high‐risk condition. Due to COVID‐19 exposure concerns, 23.8% had avoided prenatal care and 7.5% planned to avoid hospital delivery. Over half the women in the Guatemalan site and 40% in the Pakistan site reduced care seeking due to COVID‐19 exposure concerns. Of the women, 24.0% were afraid of getting COVID‐19 from healthcare providers. Overall, 63.3% reported wearing a mask and 29.1% planned to stay at home to reduce COVID‐19 exposure risk. Conclusions: We found a decrease in planned antenatal and delivery care use due to COVID‐19 concerns. The clinical implications of potential decreases in care are unclear, but decline in essential healthcare utilisation during pregnancy and delivery could pose challenges for maternal and newborn health. More research is needed to address the impact of COVID‐19 on routine pregnancy and delivery care.